Nano - structured triboelectric nano generators for internet - of - things (IOT) applications - Ünlü, Kemal. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
In this thesis, three diﬀerent triboelectric energy harvesters were designed and manufactured. Polydimethylsiloxane (PDMS) was used as triboelectric surface in the ﬁrst of these harvesters. In addition to untreated this surface, PDMS surfaces with polystyrene (PS) and poly(pentaﬂuorostyrene) (PPFS) nano brushes are used and com parisons of these three have been made. The eﬀective area of these three surfaces are 1 cm2. In the measurements of the PDMS surface maximum transferred power is mea sured as 45.7 nW at 300MΩ load. This value was increased by approximately 16 times for the PS sample to 750.6 nW and for the PPFS sample by 48 times to 2.3 µ W. Thus, it has been successfully shown that the nano brushing method seriously increases the triboelectric charge density. Polytetraﬂuoroethylene (PTFE) ﬁlm and steel electrode were used for the other harvesters fabricated. In the ﬁrst of the PTFE-based harvesters, the steel ﬁlm passed through the microfabrication process. In the measurements of this harvester with 1 cm2 eﬀective area, maximum transferred power is measured as 895 nW at 250MΩ load. This harvester which is designed as keyboard button shows that the batteryless keyboard can be made by using triboelectric energy harvesters. The eﬀective area of the last harvester fabricated in macro size is 60 cm2. The maximum transferred power with this harvester is measured as 203 µW at 140MΩ. This gener ated power succesfully lit up 196 commercial LED. It has also been shown that this power can be used in IoT applications that use low power bluetooth.
Keywords: Internet of things.; Code generators.; Nanotechnology.